Matching plate design technique for PZT type lamb wave transducers - Ilham Hadi Syahril (2018)
Piezoelectric transducers are widely used in defect inspections on large structures. The non-destructive inspections are typically performed on metal structures but can be applied on non-metal structures such as concretes and carbon fibre reinforced polymers. Mismatch of acoustic impedance between piezoelectric element and medium in inspections reduces the amount of ultrasonic energy emitted from the element. This ultrasonic energy reduction is due to the reflection that occurs at the interface caused by the difference in the acoustic impedance values. In addition, the signal attenuation also shortens the monitoring distance in structural health monitoring and leads to an inconsistent wave ringing or unwanted signal in the measurements. Thus, a study on the matching plate in the piezoelectric transducer is conducted to reduce the mismatch of acoustic impedance between the piezoelectric element and medium of the wave propagation. In order to achieve higher transmission of ultrasonic energy into the propagating medium, single layer and multilayer matching plates are placed between the active piezoelectric element and medium of the wave propagation. Two different design techniques were performed to obtain a single layer matching plate by using quarter wavelength and group velocity dispersion techniques. Evaluations on the quarter wavelength and group velocity dispersion techniques were carried out on single layer matching plates using a developed model in ABAQUS. The evaluations on matching plates of aluminium, brass, copper, and acrylic were performed at different thicknesses that obtained from both techniques. Assessments on time waveforms, Fast Fourier Transforms, and visualizations of the transmitted waves into the propagating medium have been made to measure the performance of the matching plates. The results indicate good transmission waves into the propagating medium from the single layer matching plates which are designed from the behaviour of the group velocity dispersion curves. The group velocity dispersion curves which are used as the guideline in selection of the suitable matching layer for the wave transmission have been applied into matching plate designs for two, three and four layers of multilayer matching plates. The simulation results are also compared to the results from single layer matching plates which are designed from the dispersion curve technique. The results show high transmission of ultrasonic energy for the matching plates with small dispersions in group velocities. At the end, the study indicates feasibility development of matching plates based on the properties of the plotted dispersion curves.